Increased pathogenicity of an Ehrlichia-like agent after passage through Amblyomma hebraeum: a preliminary report - du Plessis, J L (Onderstepoort journal of veterinary research, 1990)
After being passaged through 3 generations of Amblyomma hebraeum, an Ehrlichia-like agent isolated from an adult Hyalomma truncatum female became more pathogenic and elicited a disease in sheep indistinguishable from heartwater. Cross-immunity between this agent and several stocks of Cowdria ruminantium and high levels of antibody elicited by the agent against 2 stocks of C. ruminantium in the indirect fluorescent antibody test, confirmed its close relationship to Cowdria.